A europium MOFs material composite fluorescent probe containing carbon dots and preparation and detection method thereof
By using the europium MOFs material containing carbon dots as a composite fluorescence probe, the problems of insufficient sensitivity and poor light stability in the existing HOCl detection methods are solved, and sensitive selectivity detection and high reliability detection of HOCl in water samples are achieved.
Patent Information
- Application Number
- CN202311097988.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-08-29
AI Technical Summary
The existing HOCl detection methods have problems such as insufficient sensitivity, poor light stability and low detection reliability, especially in the detection of HOCl in water samples.
The europium MOFs material containing carbon dots is used as a composite fluorescence probe. By encapsulating the carbon dots and surface modification of the lanthanide metal ions, the ratio fluorescence detection of HOCl is achieved, which improves the detection reliability and improves the light stability of the carbon dots in aqueous solution.
Sensitive selective detection of HOCl is realized, the detection reliability and light stability are improved, and the concentration of HOCl in water samples can be effectively detected.
Smart Images

Figure CN117165290B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for detecting hypochlorous acid (HOCl), and in particular to a method for detecting HOCl based on a europium MOFs material containing carbon dots as a composite fluorescent probe, and belongs to the field of analysis and environmental monitoring. Background Art
[0002] Hypochlorous acid (HOCl), as an important reactive oxygen species, is formed by the reaction of hydrogen peroxide and chloride ions catalyzed by myeloperoxidase (MPO) in cells. It is also related to various diseases such as inflammatory diseases, cardiovascular diseases, kidney diseases, acute lung injury and even cancer. In addition, the chlorine disinfection process of tap water will produce hypochlorous acid. Therefore, the detection of hypochlorous acid concentration in water samples or living cells is of great significance.
[0003] At present, traditional HOCl detection methods include iodine titration, phosphorescence, colorimetry, electrochemistry, high performance liquid chromatography and fluorescence, among which fluorescence has received increasing attention in the development of sensors for real-time biological monitoring due to its rapid response, high sensitivity and excellent fluorescence imaging capabilities. In the fluorescence method, carbon dot fluorescent probes have attracted attention due to their easy preparation, non-toxicity or low toxicity, and good biocompatibility. Compared with the existing carbon dot fluorescent probes for determining HOCl, the present invention has the following advantages: most carbon dot fluorescent probes have a single emission peak, while ratio fluorescent probes can be internally corrected through multiple fluorescence emission peaks to improve the reliability of detection. The MOFs of the present invention achieve ratio fluorescence detection of analytes by encapsulating carbon dots and surface modification of lanthanide metal ions. In addition, the encapsulation of carbon dots by MOFs is also beneficial to improving the photostability and photobleaching performance of carbon dots in aqueous solution. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects in the prior art and provide a europium MOFs material composite fluorescent probe containing carbon dots and a preparation and detection method thereof.
[0005] The specific technical solutions adopted by the present invention are as follows:
[0006] In the first aspect, the present invention provides a method for preparing a composite fluorescent probe of europium MOFs material containing carbon dots, which is as follows:
[0007] S1: Dissolve pyromellitic acid in water, then add nitrogen-doped carbon dot aqueous solution and zirconium tetrachloride aqueous solution in sequence; stir the resulting mixed solution under high temperature and reflux, cool to room temperature and centrifuge to collect the precipitate, wash the precipitate and vacuum dry to obtain a yellow-brown solid powder N-CDs@UiO-66-(COOH)2;
[0008] S2: Disperse the obtained N-CDs@UiO-66-(COOH)2 and europium chloride hexahydrate in water, stir at high temperature, centrifuge and collect the precipitate, wash the precipitate and vacuum dry it to obtain a light yellow solid powder N-CDs@Eu-UiO-66-(COOH)2, which is a europium MOFs material composite fluorescent probe encapsulating carbon dots.
[0009] Preferably, in step S1, the nitrogen-doped carbon dots are synthesized by a one-step hydrothermal method, and the preparation method is specifically as follows:
[0010] 1.0 g of citric acid monohydrate, 400.0 mg of ethylenediamine and 400.0 mg of arginine were fully mixed and dissolved in 10.0 mL of ultrapure water, and then the obtained mixed solution was transferred to a polytetrafluoroethylene-lined reactor and reacted in an oven at 220° C. for 5 h; the brown solution generated by the reaction was filtered through a 0.22 μm microporous filter membrane, and then dialyzed with cellulose ester with MW=500 for 24 h for further purification, and finally the obtained solution was dried in a freeze dryer for 18 h to obtain a dark brown solid powder, which is the nitrogen-doped carbon dots.
[0011] Preferably, the step S1 is specifically as follows:
[0012] 635.4 mg of pyromellitic acid was weighed and dissolved in 25.0 mL of ultrapure water by ultrasonication. Then 3.0 mL of 2.0 g / L nitrogen-doped carbon dot aqueous solution and 3.0 mL of 0.82 mM zirconium tetrachloride aqueous solution were added in sequence. The obtained mixed solution was stirred and refluxed at 100 °C for 18 h. After the reaction solution was cooled to room temperature, it was centrifuged at 9000 r / min for 10 min, and the precipitate was collected. The obtained precipitate was washed three times with methanol and finally placed in a vacuum drying oven at 50 °C overnight to obtain N-CDs@UiO-66-(COOH)2.
[0013] Preferably, the step S2 is specifically as follows:
[0014] 100.0 mg N-CDs@UiO-66-(COOH)2 and 583.0 mg europium chloride hexahydrate were dispersed in 10.0 mL ultrapure water and stirred at 60 °C for 24 h, then centrifuged at 9000 r / min for 10 min, and the precipitate was collected. After washing the precipitate three times with methanol, it was placed in a vacuum drying oven at 50 °C overnight to obtain N-CDs@Eu-UiO-66-(COOH)2.
[0015] In a second aspect, the present invention provides a composite fluorescent probe of europium MOFs material encapsulating carbon dots obtained by any preparation method described in the first aspect.
[0016] In a third aspect, the present invention provides a method for ratiometric fluorescence detection of HOCl using the europium MOFs material composite fluorescent probe containing carbon dots described in the second aspect, as follows:
[0017] 200.0 μL of 200.0 mM acetic acid-sodium acetate buffer solution and 10.0 μL of 10.0 g / L aqueous solution containing the carbon dot-encapsulated europium MOFs material composite fluorescent probe were mixed, and then the water sample to be tested containing HOCl was added, and the obtained mixed solution was diluted to 2.0 mL with water, and after being fully shaken, it was allowed to stand for full response to obtain a test solution; under an excitation wavelength of 335 nm, the fluorescence intensity of the test solution was measured at emission wavelengths of 440 nm and 618 nm, respectively, and the quenching efficiency (I 440 / I 618 )0 / (I 440 / I 618 ) and different concentrations of HOCl to obtain the concentration of HOCl in the water sample to be tested.
[0018] Preferably, in the test solution, the concentration of the europium MOFs material composite fluorescent probe encapsulating carbon dots is 50.0 mg / L, the pH is 6.5, and the response time is 2 min.
[0019] Preferably, in the water sample to be tested, the HOCl concentration is 0.05-5.0 μM.
[0020] Compared with the existing carbon dot fluorescent probes, the present invention has the following advantages: most CDs have a single emission peak, which is not as good as ratio fluorescent probes that can perform internal correction through multiple fluorescence emission peaks to improve the reliability of detection. The MOFs of the present invention realize ratio fluorescence detection of analytes by encapsulating CDs and surface modification of lanthanide metal ions. In addition, MOFs encapsulation of CDs is also conducive to improving the photostability and photobleaching performance of CDs in aqueous solution.
[0021] The present invention proposes a strategy for constructing a dual-emission composite fluorescent probe based on MOFs, and uses it for the sensitive and selective detection of HOCl in water samples. The dual-emission composite fluorescent probe based on MOFs first uses a hydrothermal method to prepare nitrogen-doped carbon dots (N-CDs), then N-CDs, pyromellitic acid and ZrCl4 are synthesized in one pot to form N-CDs@UiO-66-(COOH)2, and finally Eu 3+ The N-CDs@UiO-66-(COOH)2 composite fluorescent probe was obtained by functional modification. HOCl quenched the fluorescence of N-CDs by oxidizing the hydroxyl groups on N-CDs. 3+The luminescence comes from the antenna effect of MOFs and remains unchanged, and the response of the N-CDs@Eu-UiO-66-(COOH)2 composite fluorescent probe to HOCl is not affected by other interfering substances. The probe has been successfully used to detect the concentration of HOCl in actual environmental water samples. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The fluorescence spectrum of the N-CDs@Eu-UiO-66-(COOH)2 composite fluorescent probe. Acetic acid-sodium acetate buffer: 20.0 mM, pH = 6.5, λ ex =335nm.
[0023] Figure 2 The effects of assay conditions on HOCl assay, including (A) the effect of probe concentration on fluorescence quenching efficiency, (B) the effect of pH on fluorescence intensity, (C) the effect of pH on fluorescence quenching efficiency, and (D) the effect of response time on fluorescence quenching efficiency.
[0024] Figure 3 is the fluorescence ratio (I 440 / I 618 )0 / (I 440 / I 618 ) and HOCl concentration.
[0025] Figure 4 The selectivity of N-CDs@Eu-UiO-66-(COOH)2 composite fluorescent probe for HOCl detection. (A) The effect of the test component on the fluorescence quenching efficiency, (B) The effect of HOCl and the test component coexisting on the fluorescence quenching efficiency. DETAILED DESCRIPTION
[0026] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0027] The present invention provides a method for preparing a composite fluorescent probe of europium MOFs material containing carbon dots, which is specifically as follows:
[0028] S1: Preparation of N-CDs@UiO-66-(COOH)2:
[0029] Dissolve pyromellitic acid in water, and then add nitrogen-doped carbon dots (N-CDs) aqueous solution and zirconium tetrachloride (ZrCl4) aqueous solution in sequence; stir and reflux the obtained mixed solution at high temperature, cool to room temperature and then centrifuge to collect the precipitate, wash the precipitate and vacuum dry to obtain a yellow-brown solid powder N-CDs@UiO-66-(COOH)2.
[0030] In this embodiment, the steps are as follows:
[0031] Weigh 635.4 mg of pyromellitic acid and dissolve it in 25.0 mL of ultrapure water by ultrasonication. Then add 3.0 mL of 2.0 g / L N-CDs solution and 3.0 mL of 0.82 mM ZrCl4 solution in sequence, and stir and reflux the mixed solution at 100 °C for 18 h. After the reaction solution is cooled to room temperature, centrifuge for 10 min (9000 r / min) to collect the precipitate. The precipitate is washed three times with methanol and finally placed in a vacuum drying oven at 50 °C overnight to obtain a yellow-brown solid powder N-CDs@UiO-66-(COOH)2.
[0032] S2: Preparation of N-CDs@Eu-UiO-66-(COOH)2:
[0033] The N-CDs@UiO-66-(COOH)2 obtained in step S1 and europium chloride hexahydrate are dispersed in water, stirred at high temperature, centrifuged and the precipitate is collected, the precipitate is washed and vacuum dried to obtain a light yellow solid powder N-CDs@Eu-UiO-66-(COOH)2, which is a europium MOFs material composite fluorescent probe encapsulating carbon dots.
[0034] In this embodiment, the steps are as follows:
[0035] Weigh 100.0 mg N-CDs@UiO-66-(COOH)2 and 583.0 mg europium chloride hexahydrate and disperse them in 10.0 mL ultrapure water, stir at 60 °C for 24 h, then centrifuge for 10 min (9000 r / min) to collect the precipitate, wash the precipitate three times with methanol and place it in a 50 °C vacuum oven overnight to obtain a light yellow solid powder N-CDs@Eu-UiO-66-(COOH)2. Weigh a certain amount of N-CDs@Eu-UiO-66-(COOH)2 solid powder and disperse it with 10.0 mL ultrapure water to obtain a 10.0 g / L N-CDs@Eu-UiO-66-(COOH)2 composite fluorescent probe stock solution.
[0036] S3: Ratiometric fluorescence detection of HOCl by composite fluorescent probe:
[0037] 200.0 μL of 200.0 mM acetic acid-sodium acetate buffer solution (pH 6.5) and 10.0 μL of 10.0 g / L aqueous solution containing the europium MOFs material composite fluorescent probe containing carbon dots are mixed, and then added to a centrifuge tube, and then a water sample to be tested containing HOCl (HOCl concentration is 0.05-5.0 μM) is added, and the resulting mixed solution is fixed to 2.0 mL with water (at this time, the concentration of the europium MOFs material composite fluorescent probe containing carbon dots is 50.0 mg / L), and after being fully shaken, it is allowed to stand for full response to obtain a test solution; at an excitation wavelength of 335 nm, the fluorescence intensity of the test solution is measured at emission wavelengths of 440 nm and 618 nm, respectively, and at the same time, the quenching efficiency (I 440 / I 618 )0 / (I 440 / I 618 ) and different concentrations of HOCl to obtain the concentration of HOCl in the water sample to be tested.
[0038] 1. Fluorescence response of N-CDs@Eu-UiO-66-(COOH)2 composite fluorescent probe to hypochlorous acid
[0039] The fluorescence spectrum of the dual-emission fluorescent probe N-CDs@Eu-UiO-66-(COOH)2 (i.e., the europium MOFs material composite fluorescent probe containing carbon dots) constructed by the above method is as follows: Figure 1 As shown. Under 335nm excitation, the fluorescence peak of N-CDs is at 440nm, and Eu 3+ The characteristic fluorescence peaks emitted are at 596nm, 618nm and 700nm, corresponding to Eu 3+ of 5 D0→ 7 F J (J=1, 2, 4) orbital transition, this transition comes from the "antenna effect". After HOCl is added to the system, the fluorescence peak at 440nm is quenched, and Eu 3+ The characteristic fluorescence peak of HClO hardly changes, so it can be used as an internal standard to construct a ratiometric fluorescence probe for sensitive detection of HClO.
[0040] 2. Optimization of the determination conditions of N-CDs@Eu-UiO-66-(COOH)2 composite fluorescence probe
[0041] The detection conditions (including probe concentration, pH and response time) of the europium MOFs material composite fluorescent probe containing carbon dots constructed above were optimized. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the optimal measurement conditions are a probe concentration of 50.0 mg / L, a pH of 6.5, and a response time of 2 min.
[0042] 3. Quantitative detection of hypochlorous acid using N-CDs@Eu-UiO-66-(COOH)2 composite fluorescent probe
[0043] Under the optimized experimental conditions, the probe was tested for quantitative detection of hypochlorous acid. The results are as follows: Figure 3 When the HOCl concentration is in the range of 0.05 to 3.0 μM, the quenching efficiency of the ratiometric fluorescent probe (I 440 / I 618 )0 / (I 440 / I 618 ) has a good linear relationship with the HOCl concentration, and the linear equation is (I 440 / I 618 )0 / (I 440 / I 618 )=0.4589[HOCl]+1.0008(R 2 =0.9965), the detection limit (LOD) is 15.0nM (3σ / K). 440 / I 618 )0 is the fluorescence intensity of the blank sample.
[0044] 4. Selectivity of N-CDs@Eu-UiO-66-(COOH)2 composite fluorescent probe for hypochlorous acid
[0045] In order to investigate the selectivity of the probe obtained by the above method for hypochlorous acid, the following common ions (such as Zn 2+ , Ca 2+ Mg 2+ , Fe 3+ , Fe 2+ PO4 3- , Cl - 、NO2 - 、NO3 - and other active small molecules such as AA, GSH, H2O2, OH, 1 O2, NO·, ONOO - , TBHP, O t Bu) on the probe detection, the results are as follows Figure 4 As shown. Figure 4 It can be seen that these substances have no obvious effect on the fluorescence intensity of the system, so the N-CDs@Eu-UiO-66-(COOH)2 probe has good selectivity for the detection of hypochlorous acid.
[0046] 5. Detection and application of HOCl in actual water samples
[0047] Six water samples were collected, including two groups of tap water, two groups of lake water and two groups of swimming pool water. After simple filtration, the HOCl in the water samples was detected by the method of the present invention, and the standard method DPD colorimetry was used for verification. The results are shown in Table 1. HOCl was detected in all water samples, and the results were compared. The results were basically consistent, indicating that the detection method of the present invention can be used as an effective and reliable tool for monitoring HOCl in environmental water samples.
[0048] Table 1 Detection of HOCl in actual water samples
[0049]
[0050] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A ratio fluorescence detection method for HOCl using a europium MOFs material composite fluorescent probe containing carbon dots, characterized in that: The preparation method of the europium MOFs material composite fluorescent probe containing carbon dots is as follows: S1: Dissolve pyromellitic acid in water, then add nitrogen-doped carbon dots aqueous solution and zirconium tetrachloride aqueous solution in sequence; stir the resulting mixed solution at 100°C for reflux, cool to room temperature, centrifuge and collect the precipitate, wash the precipitate and vacuum dry to obtain a yellow-brown solid powder N-CDs@UiO-66-(COOH)2; S2: Disperse the obtained N-CDs@UiO-66-(COOH)2 and europium chloride hexahydrate in water, stir at 60°C, centrifuge and collect the precipitate, wash the precipitate and vacuum dry it to obtain a light yellow solid powder N-CDs@Eu-UiO-66-(COOH)2, which is a europium MOFs material composite fluorescent probe encapsulating carbon dots; In step S1, nitrogen-doped carbon dots are synthesized by a one-step hydrothermal method, and the preparation method is specifically as follows: 1.0 g of citric acid monohydrate, 400.0 mg of ethylenediamine and 400.0 mg of arginine were fully mixed and dissolved in 10.0 mL of ultrapure water, and then the obtained mixed solution was transferred to a polytetrafluoroethylene-lined reactor and reacted in an oven at 220° C. for 5 h; the brown solution generated by the reaction was filtered through a 0.22 μm microporous filter membrane, and then dialyzed with cellulose ester with MW=500 for 24 h for further purification, and finally the obtained solution was dried in a freeze dryer for 18 h to obtain a dark brown solid powder, which is nitrogen-doped carbon dots; The ratio fluorescence detection method is specifically as follows: 200.0 μL of 200.0 mM acetic acid-sodium acetate buffer solution and 10.0 μL of 10.0 g / L aqueous solution containing the carbon dot-encapsulated europium MOFs material composite fluorescent probe were mixed, and then the water sample to be tested containing HOCl was added, and the obtained mixed solution was diluted to 2.0 mL with water, and after being fully shaken, it was allowed to stand for full response to obtain a test solution; under an excitation wavelength of 335 nm, the fluorescence intensity of the test solution was measured at emission wavelengths of 440 nm and 618 nm, respectively, and the quenching efficiency (I 440 / I 618 )0 / (I 440 / I 618 ) and different concentrations of HOCl to obtain the concentration of HOCl in the water sample to be tested.
2. The ratio fluorescence detection method of HOCl using a europium MOFs material composite fluorescent probe containing carbon dots according to claim 1, characterized in that: The step S1 is specifically as follows: 635.4 mg of pyromellitic acid was weighed and dissolved in 25.0 mL of ultrapure water by ultrasonication. Then 3.0 mL of 2.0 g / L nitrogen-doped carbon dot aqueous solution and 3.0 mL of 0.82 mM zirconium tetrachloride aqueous solution were added in sequence. The obtained mixed solution was stirred and refluxed at 100 °C for 18 h. After the reaction solution was cooled to room temperature, it was centrifuged at 9000 r / min for 10 min, and the precipitate was collected. The obtained precipitate was washed three times with methanol and finally placed in a vacuum drying oven at 50 °C overnight to obtain N-CDs@UiO-66-(COOH)2.
3. The ratio fluorescence detection method of HOCl using a europium MOFs material composite fluorescent probe containing carbon dots according to claim 1, characterized in that: The step S2 is specifically as follows: 100.0 mg N-CDs@UiO-66-(COOH)2 and 583.0 mg europium chloride hexahydrate were dispersed in 10.0 mL ultrapure water and stirred at 60 °C for 24 h, then centrifuged at 9000 r / min for 10 min, and the precipitate was collected. After washing the precipitate three times with methanol, it was placed in a vacuum drying oven at 50 °C overnight to obtain N-CDs@Eu-UiO-66-(COOH)2.
4. The ratio fluorescence detection method of HOCl using a europium MOFs material composite fluorescent probe containing carbon dots according to claim 1, characterized in that: In the test solution, the concentration of the europium MOFs material composite fluorescent probe containing carbon dots is 50.0 mg / L, the pH is 6.5, and the response time is 2 min.
5. The ratio fluorescence detection method of HOCl using a europium MOFs material composite fluorescent probe containing carbon dots according to claim 1, characterized in that: In the water sample to be tested, the HOCl concentration is 0.05-5.0 μM.
Citation Information
Patent Citations
Preparation method of dual-emission colorimetric fluorescence nano-microsphere and application of nano-microsphere in bacterial detection
CN109490269A
Carbon quantum dot compounded UiO-66 derivative capable of being used for trace Cu 2+ ion detection
CN113429960A